2015
DOI: 10.1039/c5ra08405a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mesoporous silica nanoparticle surface chemistry and concentration on the α-synuclein fibrillation

Abstract: The aggregation of an amyloid protein, a-synuclein (a-Syn), has been suggested as a potential cause of Parkinson's and several other neurodegenerative diseases. To explore the possibility of using nanoparticle-based therapeutic agents for the treatment of such diseases, we investigated the influence of surface chemistry and concentration of mesoporous silica nanoparticles (MSNPs) on the fibrillation of recombinant human a-Syn protein in the present work. Bare MSNPs as well as MSNPs of different surface functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
2
23
1
Order By: Relevance
“…This is due to the fact that DLS analysis measures the hydrodynamic size of the particles, which is usually larger than the actual size of the particles. The mean pore diameter and specific surface area as measured in our previous studies 27,30,35 , are 4.1 nm and 882.1 m 2 g -1 , respectively. In those works, it was shown that the as-prepared MSNs present a structure of MCM-41 27,30,35 , which have channel-like pores 26 .…”
Section: Characterization Of Msnsmentioning
confidence: 63%
See 1 more Smart Citation
“…This is due to the fact that DLS analysis measures the hydrodynamic size of the particles, which is usually larger than the actual size of the particles. The mean pore diameter and specific surface area as measured in our previous studies 27,30,35 , are 4.1 nm and 882.1 m 2 g -1 , respectively. In those works, it was shown that the as-prepared MSNs present a structure of MCM-41 27,30,35 , which have channel-like pores 26 .…”
Section: Characterization Of Msnsmentioning
confidence: 63%
“…The MSNs were prepared and functionalized according to a previously reported approach based on the template removing method 30 . In brief, 100 mg of CTAB and 350 µL of sodium hydroxide aqueous solution (2 M) were added to 48.65 mL of water at 80 o C with constant stirring.…”
Section: Synthesis and Surface Modification Of Msnsmentioning
confidence: 99%
“…The results of fluorescence microscopy are also demonstrated in Figure D. Samples containing fibrils are almost transparent in visible light; however, by coloring with ThT, fibrils can be seen and identified under the fluorescence microscope as extended particles (Ban and Goto, ; Taebnia and others ). Extended particles were observed in the fluorescence images of both untreated samples and those treated with spermidine, while only small and dispersed particles could be seen in the fluorescence images of the sample incubated in the presence of cuminaldehyde (Figure D).…”
Section: Resultsmentioning
confidence: 84%
“…A plethora of evidence suggests that the nanostructures can influence protein fibrillation depending on various conditions, including the coating, size, surface charge, and concentration. Such discrepancy has been seen for example in silica-based nanoparticles, where positively charged silica nanoparticles inhibited α -syn fibrillation and negatively charged one had an opposite effect [ 67 ]. Also, it was also established that SiO 2 NPs upregulate α -syn expression, inhibit protein levels of the ubiquitin-proteasome system, and induce autophagy by interference in the PI3K-Akt-mTOR signalling pathway [ 68 ].…”
Section: The Dark Side Of the Nanoparticles With A Useful Outcomementioning
confidence: 99%